HASTANE KAYNAKLI (Nozokomiyal) MANTAR İNFEKSİYONLARININ EPİDEMİYOLOJİSİ - YÜCEL, Ayhan; KANTARCIOĞLU, A. Serda (Cerrahpaşa Medical Journal, 2014)
Background.- Nosocomial fungal infections have became important causes of morbidity and mortality over the last ten years. Immunocompromised patients are at a high risk of hospital acquired fungal infections, specially candidemia. Epidemiology of nosocomial fungal infections concerning on frequently isolated causative agents and major risk factors have been reviewed in this paper.